Digital Services Tax : Country Practice and Technical Challenges - Cebreiro-Gomez, Ana (World Bank, Washington, DC, 2022)
Digital platforms are transforming social, business, and economic norms, changing theway we interact, consume, and do business. Digital technologies present many opportunitiesand benefits for society and governments. They also provide new opportunities for taxadministrations, such as prospects for better and more efficient tax collection by accessing newdata sources and improved international collaboration.